Innovating with teleworking in practical training - Sandoval Cruz, Estefania
Information and Communication Technologies are not being exploited in such an updated world, the entrepreneurhas not entered the wavelength of technologies to make the most of the human resource that allows him toobtain greater profits for the organization, and this is why this research has identified that Teleworking has notyet been implemented in a decisive way regarding SENA apprentices, preventing the evolution of training in thisinnovation dynamic.These technologies allow the interaction of cultures, the creation of new knowledge and the sharing of experiencesthat bring different people closer together in any part of the world, through different means of learning that arereachable in this technological era.Teleworking as a form of work organization is an inclusive alternative that ratifies flexible inclusion in theworkplace, which is why this research wants to show the results on: ¿Why companies have not taken the decisionto include Teleworking with SENA apprentices? with the sole purpose of exhorting employers to take the risk inusing new forms of work that can bring benefits for the parties.The methodology used for this research was descriptive-qualitative, which allows to know the characteristics of asample before a specific situation, for the collection of data, online surveys and in-depth expert interviews werecarried out.Finally, the main factors that must be worked by educational institutions, companies and responsible entitiesfor the promotion of Teleworking in Colombia are shown, as well as, alternatives are proposed to achievethe implementation of Teleworking safely within the Learning Contract, generating innovation in both theapprentice’s practical training and the administrative processes of the companies.